Surgical challenges, novel techniques, and systemic treatment of giant cell tumour of bone of the distal radius: clinical outcomes and systematic review of the literature. (1st July 2022) - van der Heijden, Lizz; Bindt, Sjaan; Scorianz, Maurizio; Ng, Colin; Gibbons, Max C. L. H.; van de Sande, Michiel A. J.; Campanacci, Domenico A.
Abstract : Aims: Giant cell tumour of bone (GCTB) treatment changed since the introduction of denosumab from purely surgical towards a multidisciplinary approach, with recent concerns of higher recurrence rates after denosumab. We evaluated oncological, surgical, and functional outcomes for distal radius GCTB, with a critically appraised systematic literature review. Methods: We included 76 patients with distal radius GCTB in three sarcoma centres (1990 to 2019). Median follow-up was 8.8 years (2 to 23). Seven patients underwent curettage, 38 curettage with adjuvants, and 31 resection; 20 had denosumab. Results: Recurrence rate was 71% (5/7) after curettage, 32% (12/38) after curettage with adjuvants, and 6% (2/31) after resection. Median time to recurrence was 17 months (4 to 77). Recurrences were treated with curettage with adjuvants (11), resection (six), or curettage (two). Overall, 84% (38/45) was cured after one to thee intralesional procedures. Seven patients had 12 months neoadjuvant denosumab (5 to 15) and sixmonths adjuvant denosumab; two recurred (29%). Twelve patients had six months neoadjuvant denosumab (4 to 10); five recurred (42%). Two had pulmonary metastases (2.6%), both stable after denosumab. Complication rate was 18% (14/76, with 11 requiring surgery). At follow-up, median MusculoSkeletal Tumour Society score was 28 (18 to 30), median Short Form-36 Health Survey was 86 (41 to 95), and median Disability of Arm, Shoulder, and Hand was 7.8 (0 to 58). Conclusion: Distal radius GCTB treatment might deviate from general GCTB treatment because of complexity of wrist anatomy and function. Novel insights on surgical treatment are presented in this multicentre study and systematic review. Intralesional surgery resulted in high recurrence-rate for distal radius GCTB, also with additional denosumab. The large majority of patients however, were cured after repeated curettage. Cite this article: Bone Jt Open  2022;3(7):515–528.